Some service problems of turbine blades: Factors affecting diagnosis and correction - Rieger, Neville (Revista Técnica da Faculdade de Engenharia da de Zulia)
This paper discusses several important types of turbine blading failure. A review of the basic causes of blading failures, e.g. fatigue, corrosion, stress corrosion cracking, erosion, etc., is given. Procedures for calculating stresses associated with such failures and the numbers of cycles to failure are reviewed. The familiar Goodman diagram procedure for cycles to rack initiation in included, plus a fracture mechanics approach to give the number of propagation cycles. Four case histories of turbine blade failure are described in detail, in clouding operating conditions, diagnostic procedures used, determination of failure cause, and remedies chosen to avoid further blading failures, in each case 13 references to the subject literature are given.